2003
DOI: 10.1021/np030195z
|View full text |Cite
|
Sign up to set email alerts
|

Homogentisic Acid Derivatives from Miliusa balansae

Abstract: The new homogentisic acid derivatives miliusol (1b) and miliusolide (2) from Miliusa balansae were isolated and structurally determined by spectroscopic means. The relative configurations of the new 1b and its known acetate 1a were established. Furthermore, the symmetric ether bis(2-hydroxyphenyl)methyl ether 3, which was isolated for the first time from a natural source, the known flavonoids pachypodol and chrysosplenol C, and sodium benzoate were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 6 publications
0
36
0
Order By: Relevance
“…This plant is used for gastropathy and glomerulonephropathy in Chinese traditional medicine [1]. From this plant three homogentisic acid derivatives, miliusate [1,2], miliusol and miliusolid [3], four flavanones, two dihydrochalcones and two styryl derivatives [2] were isolated. In this paper the isolation and structure determination of two new bis-styryl compounds (2, 3) are described.…”
Section: Introductionmentioning
confidence: 99%
“…This plant is used for gastropathy and glomerulonephropathy in Chinese traditional medicine [1]. From this plant three homogentisic acid derivatives, miliusate [1,2], miliusol and miliusolid [3], four flavanones, two dihydrochalcones and two styryl derivatives [2] were isolated. In this paper the isolation and structure determination of two new bis-styryl compounds (2, 3) are described.…”
Section: Introductionmentioning
confidence: 99%
“…7 In Chinese traditional medicine, this plant is used to treat various diseases, such as gastropathy and glomerulonephropathy. 8 In previous studies, the main constituents of M. balansae have resulted in the isolation of a variety of secondary metabolites, including flavonoids, 9 dihydrochalcones, 10 styryl derivatives, 11 homogentistic acid derivatives, 12 norditerpenes, 13 and alkaloids. 14 Published investigations have previously demonstrated that this type of compound possesses several interesting cytotoxic effects.…”
mentioning
confidence: 99%
“…On the basis of spectral data and chemical evidence in agreement with those reported in the literature, the other compounds were identified as myrsinionoside D (4), 19 ampelopsisionoside (5), 20 myrsinionoside A (6), 19 threo-and erythro-1-C-syringylglycerol (7 and 8), 21 threo-and erythro-guaiacylglycerol (9 and 10), 22 (L)-guaiacyl glycerol 2 0 -O-b-D-glucopyranoside (11), 23 curcolide (12), serralactone (13), 24 b-D-glucopyranosyl (Z)-3-hexenol (14), 25 1-(3-methylbutyryl)phloroglucinol-glucopyranoside (15), 26 (À) epicatechin (16), 27 chrysosplenol C (17), 12 and rutin (18) 28 (see Fig. 1).…”
mentioning
confidence: 99%
“…Thus, on the basis of ATPase activation concept, we screened 18 compounds from the natural sources. Our efforts brought to light chrysosplenol C 19 (4′,5,6-trihydroxy-3,3′,7-trimethoxyflavone, Figure 1), a known flavonoid isolated from Miliusa balansae and Pterocaulon sphacelatum, which induced positive inotropic effect in rat ventricular myocytes by reversibly increasing ventricular cell shortening with an EC 50 value of about 45 ± 7.8 μM independent of β-adrenergic signaling 20 and showed the activation (28.1% at 10 μM) of cardiac myosin ATPase as presented in Table 1. Thus, the positive inotropic effect of Chrysosplenol C was considered to be originated from the activation of cardiac myosin ATPase.…”
mentioning
confidence: 99%